Konsep Kepemimpinan Dalam Islam dan Perannya Dalam Penegakan Keadilan: Analisis Dalam Konteks Kontemporer - Gifa Nur Syahara; Sri Wulan Rambe; Syawaliyah Fitri; Fauzan Azhima; Zahra Qanita Sukmawardani (Yayasan Dar Arrisyah Indonesia, 2026)
Leadership occupies a central position in Islamic political and social thought, particularly in relation to the realization of justice and public welfare. However, contemporary studies on Islamic leadership tend to focus on normative and theological discussions without sufficiently connecting Islamic leadership principles to the challenges of modern governance. This study aims to analyze the concept of leadership in Islam, examine its role in the enforcement of justice, and reconstruct its relevance within contemporary governance frameworks. Employing a qualitative library research approach, this study analyzes primary Islamic sources, including the Qur'an and Hadith, alongside classical and contemporary scholarly works on Islamic leadership.The findings reveal that Islamic leadership is fundamentally grounded in the principles of trustworthiness (amanah), justice (al-'adl), consultation (shura), accountability (al-mas'uliyyah), and public welfare (maslahah). These principles position leadership not merely as political authority but as a moral and ethical responsibility. Furthermore, the study argues that Islamic leadership can be reconstructed as an ethical leadership paradigm that aligns with contemporary governance principles such as accountability, participatory decision-making, transparency, and social justice. This reconstruction constitutes the main contribution of the study by demonstrating that Islamic leadership is not only a normative religious concept but also a relevant framework for addressing current challenges of governance, including corruption, abuse of power, and declining public trust in institutions. The study concludes that the values of Islamic leadership remain highly relevant in contemporary society and can contribute significantly to the development of ethical, accountable, and justice-oriented governance systems. Future research is recommended to explore the empirical implementation of Islamic leadership principles in governmental, educational, and social institutions.